The Effect of Immersion in Water on Some Blood & Physiological Parameters in Rats - Selim, Salah I.; DH, Wasfi . Abdali; Rashad, Hussein M.; Ibrahim, F. M (Al-Mukhtar Journal of Sciences, 2008)
This study was carried out using 21albino rats with the same age and weighted from 250-300 gm and subdivided into 3 groups. The first group 7 rats as control group, The second group 7 rats was immersed in glass gar containing war water at 40°C until the neck for 2 hours. The third group was immersed in glass jar containing water at 4°C and treated similar to the second group. The rats were slaughtered immediately at the end of the experiment period, blood samples were collected, then the following were measured: Alkaline phosphatase concentration, RBCs count, Hb concentration, sodium, potassium, calcium ,phosphorous concentration and testosterone hormone level. The data investigate slightly significant decrease in alkaline phosphate concentration and testosterone hormone concentration and little decrease in RBCs count and Hb concentration as well as decrease in Na+ ,k+ , concentration and significant increase in Ca++ and phosphorus concentration . The study is concluded that the stress of immersion in worm and cold has a negative effects on the alkaline phosphatase ,testosterone , RBCs count , Hb, Na+, k +, and positive effects on Ca++ and phosphorous.